WAYANG KULIT SEBAGAI MEDIA DAKWAH KI ANOM SUROTO - Alip Nuryanto; Saepullah Saepullah (Pascasarjana IAIN Metro, 2020)
Ki Anom Suroto, with his religious beliefs, has an influence on the wayang performances performed. One of them can be seen clearly in the song or song Pepeling and the story or play of Makutarama. Ki Anom Suroto is very concerned about communication that is easily understood by the community. Ki Anom Suroto's puppeteer style is very much influenced by the styles of Surakarta, Yogyakarta and Banyumasan. The purpose of this research is to find out the life history of Ki Anom Suroto how it can influence the play in the Ki Anom puppet show. Suroto, how da'wah colors the story or play masterminded by Ki Anom Suroto, and how is the communication made by Ki Anom Suroto in the puppet show. This study is a study using two data sources. The first data is primary data obtained from interviews, observations, and document studies that are directly related to Ki Anom Suroto's environment. The second data is secondary data obtained from books, journals or articles that support this research. The approach used in this study is the historical story approach and the communication approach of Romy L. Romodirjo, and to analyze the data using the interpretation method. The conclusion of this study is that the history of past life is very influential on the next life. The next life will be stable if you can adjust yourself through communication in accordance with the situation and conditions that are being passed.